Dual Free Radical Synergism for Enhancing Proton Conductivity in Photochromism iHOFs - Liu, Cheng; Chen, Xu-Yong; Cao, Xiao-Jie; Zhang, Wenmin; Cao, Li-Hui (Precision Chemistry, 2025)
Stimuli-responsive smart materials, as an emerging material, can fulfill reversible transformation of chemical/physical properties under external stimuli such as mechanical stress, light, and electricity, which has the highlights of rapid response, designable structure, and function. Two ionic hydrogen-bonded organic frameworks (iHOFs 36–37) were synthesized by self-assembly of bis(benzene-o/p-sulfonic acid)-naphthalenediimide (o/p-H2BSNDI) and two basic ligands. The naphthalenediimide (NDI) was introduced into the material to equip iHOFs 36–37 with radical-driven photochromic behavior. The proton conductivity of iHOF-37 demonstrated a maximum of 6.50 × 10–4 S·cm–1 at 98% RH and 100 °C, and it increased to 9.10 × 10–3 S·cm–1 due to dual free radical synergism following UV irradiation (NDI and viologen), which represents a significant 14-fold enhancement. Furthermore, the incorporation of iHOF-37 into the chitosan (CS) matrix forms photochromic composite membranes. The proton conductivity of the 5%-iHOF-37/CS composite membrane reached up to 5.70 × 10–2 S·cm–1 at 98% RH and 90 °C, and reached 8.08 × 10–2 S·cm–1 after UV irradiation. This work reveals the dual radicals generated by NDI and viologen derivatives, whose synergistic action plays a significant role in enhancing the proton conductivity in iHOFs and composite membranes, rendering the rational design of stimuli-responsive smart materials feasible.